Grouper RIP2 inhibits Singapore grouper iridovirus infection by modulating ASC-caspase-1 interaction - Zhang, Xin; Wu, Siting; Liu, Zetian; Chen, Hong; Liao, Jiaming; Wei, Jingguang; Qin, Qiwei (Frontiers in Immunology, 2023)
Introduction Receptor interacting protein 2 (RIP2), serves as a vital sensor of cell stress, is able to respond to cell survival or inflammation, and is involved in antiviral pathways. However, studies on the property of RIP2 in viral infections in fish have not been reported. Methods In this paper, we cloned and characterized RIP2 homolog from orange-spotted grouper (Epinephelus coioides) (EcRIP2) and further discussed the relevance of EcRIP2 to EcASC, comparing the influences of EcRIP2 and EcASC on the modulation of inflammatory factors and the NF-κB activation to reveal the mechanism of EcRIP2 in fish DNA virus infection. Results Encoded a 602 amino acid protein, EcRIP2 contained two structural domains: S-TKc and CARD. Subcellular localization signified that EcRIP2 existed in cytoplasmic filaments and dot aggregation patterns. After SGIV infection, the EcRIP2 filaments aggregated into larger clusters near the nucleus. The infection of SGIV could notably up-regulate the transcription level of the EcRIP2 gene compared with lipopolysaccharide (LPS) and red grouper nerve necrosis virus (RGNNV). Overexpression of EcRIP2 impeded SGIV replication. The elevated expression levels of inflammatory cytokines induced by SGIV were remarkably hindered by EcRIP2 treatment in a concentration-dependent manner. In contrast, EcASC treatment could up-regulate SGIV-induced cytokine expression in the presence of EcCaspase-1. Enhancing amounts of EcRIP2 could overcome the down regulatory effect of EcASC on NF-κB. Nevertheless, increasing doses of EcASC failed to restrain the NF-κB activation in the existence of EcRIP2. Subsequently, it was validated by a co-immunoprecipitation assay that EcRIP2 dose-dependently competed with EcASC binding to EcCaspase-1. With increasing time to SGIV infection, EcCaspase-1 gradually combined with more EcRIP2 than EcASC. Discussion Collectively, this paper highlighted that EcRIP2 may impede SGIV-induced hyperinflammation by competing with EcASC for binding EcCaspase-1, thereby suppressing viral replication of SGIV. Our work supplies novel viewpoints into the modulatory mechanism of RIP2-associated pathway and offers a novel view of RIP2-mediated fish diseases.